2012
DOI: 10.1007/s13361-012-0376-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkali Metal Ion Cationization on Fragmentation Pathways of Triazole-Epothilone

Abstract: The collisionally activated dissociation mass spectra of the protonated and alkali metal cationized ions of a triazole-epothilone analogue were studied in a Fourier transform ion cyclotron resonance mass spectrometer. The fragmentation pathway of the protonated ion was characterized by the loss of the unit of C 3 H 4 O 3 . However, another fragmentation pathway with the loss of C 3 H 2 O 2 was identified for the complex ions with Na + , K + , Rb + , and Cs + . The branching ratio of the second pathway increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Among them, the latter four fragment ions are consistent with those observed in the CAD mass spectrum of the protonated ions of triazole-epothilone monomer 4 (m/z 505.25). [11] Previous studies of the protonated ions of 4 suggest that in their dissociation process, the bonds broken first are 1a and 1b (Scheme 1 and Scheme S1 in supporting information). Then, the formed fragment ions (m/z 417.23) can be further dissociated by breaking the bonds 1c, 1d and 1e in turn, forming fragment ions at 317.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Among them, the latter four fragment ions are consistent with those observed in the CAD mass spectrum of the protonated ions of triazole-epothilone monomer 4 (m/z 505.25). [11] Previous studies of the protonated ions of 4 suggest that in their dissociation process, the bonds broken first are 1a and 1b (Scheme 1 and Scheme S1 in supporting information). Then, the formed fragment ions (m/z 417.23) can be further dissociated by breaking the bonds 1c, 1d and 1e in turn, forming fragment ions at 317.…”
mentioning
confidence: 91%
“…This pathway is characterized by breaking the bonds 1a′ and 1b (Scheme 1). [11] It is also found that the branching ratio of this pathway increases with the increase of the size of the combined alkali metal ion. In order to better understand the effects of alkali metal ion on fragmentation pathways of compound 5 and, particularly, the intramolecular oxo-Diels-Alder reaction, the alkali metal cationized ions of 5 are studied by CAD MS, too.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, diverse interactions between different metal cations and ligand molecules allow unique structural rearrangements and dissociation pathways [31,32]. Recent studies demonstrated the effect of alkali metal and silver metal cations to generate different CID patterns [33][34][35]. In case of alkali metal cations, the ion sizes and binding properties influence the complex structures and CID patterns [33,36].…”
mentioning
confidence: 99%